Analyzing Teachers' Digital Literacy and Students' Computational Thinking Using the Streamlit Dashboard: A Case Study of PPKS Foundation Schools - Vanditya Maharani P. K.; Bernardinus Harnadi (Soegijapranata Catholic University, 2026)
Teachers’ digital literacy and students’ computational thinking (CT) skills are increasingly important in 21st-century education. Secondary data from the Assessments of “Profil Kepala Sekolah dan Guru (PPKS)” and the Bebras Challenge were used to examine the link between the two. In addition, this study develops an interactive Streamlit-based dashboard for data visualization and evaluates user perceptions of the dashboard interface. A quantitative design was used by gathering secondary data from schools connected to the PPKS Foundation. Descriptive statistics was used to summarize data of the dataset and then, correlation analysis together with simple linear regression were performed to observe the association among variables. The findings indicate that the teachers’ LD is correlated with the students’ CT skills; however, a weak to moderate relationship between them appears. The implementation of interactive visualization tool like the Streamlit dashboard helped for easy interpretation of data to be made in education. This is also supported by feedback in user interviews that described the dashboard as accessible and providing assistance to comprehend complex data.